A HiPAD Integrated with rGO/MWCNTs Nano‐Circuit Heater for Visual Point‐of‐Care Testing of SARS‐CoV‐2. (20th April 2021) - Li, Sijie; Huang, Shiyi; Ke, Yuqing; Chen, Hongjun; Dang, Jingqi; Huang, Chengjie; Liu, Wenjia; Cui, Daxiang; Wang, Jinglin; Zhi, Xiao; Ding, Xianting
Abstract: Nowadays, the main obstacle for further miniaturization and integration of nucleic acids point‐of‐care testing devices is the lack of low‐cost and high‐performance heating materials for supporting reliable nucleic acids amplification. Herein, reduced graphene oxide hybridized multi‐walled carbon nanotubes nano‐circuit integrated into an ingenious paper‐based heater is developed, which is integrated into a paper‐based analytical device (named HiPAD). The coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is still raging across the world. As a proof of concept, the HiPAD is utilized to visually detect the SARS‐CoV‐2 N gene using colored loop‐mediated isothermal amplification reaction. This HiPAD costing a few dollars has comparable detection performance to traditional nucleic acids amplifier costing thousands of dollars. The detection range is from 25 to 2.5 × 10 10 copies mL −1 in 45 min. The detection limit of 25 copies mL −1 is 40 times more sensitive than 1000 copies mL −1 in conventional real‐time PCR instruments. The disposable paper‐based chip could also avoid potential secondary transmission of COVID‐19 by convenient incineration to guarantee biosafety. The HiPAD or easily expanded M‐HiPAD (for multiplex detection) has great potential for pathogen diagnostics in resource‐limited settings. Abstract : rGO/MWCNTs are first developed into rGO/MWCNTs nano‐circuit heaters as cheap, easy‐to‐use, and flexible electrothermal modules for nucleic acid testing point‐of‐care testing devices. The miniaturized rGO/MWCNTs heater integrated paper‐based analytical device can visually detect SARS‐CoV‐2 with 25 copies mL −1 of detection limit based on colored LAMP reaction in 45 min.